Desenvolvimento e sustentação da orientação para a marca: um estudo com base na visão baseada em recursos - Magalhães, Thiago Augusto e Vasconcelos (2018)
Considering the growing importance of the corporate brand in the academic literature and the brand orientation phenomenon as a strategic organizational direction capable of generate sustainable competitive advantage, the central objective of this research was to identify which resources and capabilities of the company are strategic for the development and the support of brand orientation. It was highlighted the importance of studying the antecedents affecting brand orientation under the aspect of organizational resources, since studies that directly relate resources and capabilities to brand orientation are still limited. Besides, there is lack of Brazilian researches that investigate and analyze the existence of this orientation and its role in the national scenario. Considering the purpose of the research, it was decided to study the subject from a Resource Based View (RBV) perspective, since among the theories of strategic administration RBV places emphasis on the specific internal attributes of the organization. As for the methodological procedures, the qualitative method was adopted as use of basic technique, of a descriptive and exploratory character. Data collection was based on in-depth interviews with six brand-oriented organizations in the State of São Paulo. As data collection instrument, a semi-structured script was used, based on the literature review of this research. The data interpreted and analyzed pointed out that the resources that are related to the organizational culture, as solid and manifest fundamental values and an environment of proximity, collaboration and learning, an integrated organizational structure with focused management and key people representatives of the brand, as well as the capabilities to act consistently at the brand touchpoints and to generate emotional and symbolic benefits for stakeholders were the basis for the strategies that allowed the companies studied to develop and sustain brand orientation.